Canadian Patterns of Antimicrobial Resistance: Overview of Current Trends Related to Hospital Pathogens - Tony Mazzulli (Canadian Journal of Infectious Diseases and Medical Microbiology)
Selection of appropriate empirical antibiotic therapy is dependent on many factors, not the least of which is an understanding of antimicrobial resistance rates in the patient population that is undergoing treatment. Resistance rates may vary by geographical location, institution, hospital ward or unit, and even body site of infection. The present paper reviews the currently available Canadian data regarding resistance rates for some of the most common hospital-acquired pathogens, including Escherichia coli, Klebsiella species, Pseudomonas aeruginosa, Enterobacter species, Staphylococcus aureus and Enterococcus species. Current data suggest that the rates of extended-spectrum beta-lactamases among E coli and Klebsiella species remain relatively low across Canada. There are very little data on the epidemiology of ampC cephalosporinases among Gram-negative organisms, although combined American and Canadian data suggest that ceftazidime resistance rates for Enterobacter species range from 17.1% to 24.8%. The increased use of fluoroquinolones has led to an increase in resistance rates among most Gram-negative organisms. In the late 1990s, ciprofloxacin resistance rates for P aeruginosa were reported to be approximately 20%. For the Gram-positive organisms, methicillin resistance rates for S aureus have been reported to be as high as 10% and vancomycin resistance rates for Enterococcus species have been reported to be less than 1%. Additional data that are representative of all regions of Canada are needed. Continued surveillance, antibiotic stewardship, and adherence to good infection prevention and control measures will lead to a better understanding of the epidemiology of antimicrobial resistance in Canadian hospitals, as well as help to control its spread.